Efeito da fotobiomodulação associada ao treinamento aquático durante o processo de hipertrofia compensatória do músculo plantar em ratos wistar - Souza, Valéria de Araújo Ferreira Gregio de (2022)
Compensatory hypertrophy (CH) occurs when a mechanical overload is imposed on the muscle promoting an increase in the size of its fibers. The photobiomodulation (PBM) with low intensity laser (LLLT) showed positive results in modulating cytokines involved in muscle adaptation necessary during CH promoting an increase in cross-sectional area and improving collagen organization. The aim of this study was to evaluate the effects of aquatic training and its association with PBM on cytokine synthesis and morphological aspects of the plantar muscle during the CH process in Wistar rats. Twenty-six male Wistar rats divided into 3 groups were used: (1) Control Compensatory Hypertrophy (CH) n=6 animals; n=12 samples because the surgery is bilateral); (2) Hypertrophy + Aquatic Training (CH+AT) n=20 samples and (3) Hypertrophy + Aquatic Training + PBM (CH+AT+PBM) (n=20). Before the surgical procedure the animals underwent adaptation in AT for 5 days progressively day 1- 15min, day 2-30min, day 3- 45min, 60min the next two days. CH was induced by bilateral ablation of the plantar muscle synergist muscles lateral gastrocnemius and medial soleus. PBM was performed with AsGaAl 780 nm,10 J/cm², 40 mW, 10 s, 8 points, 3.2 J total energy. The animals performed the swimming exercises in PVC polyvinyl chloride tanks 35cm x 30cm x 30cm with a capacity of 20L and an average temperature of 31+/- 1ºC. The animals swam for 60 min/day, 5 times a week, during the 7 and 14 days. After this period, the animals were euthanized by anesthetic overdose and the plantar muscles were removed and used for weight analysis in relation to the animals' body weight, protein expression analysis of TNF -α by ELISA and pananalysis of morphological aspects including fiber diameter and cross-sectional area (CSA) by histology technique with H&E staining. Data were tested for normality by Kolmogorov-Smirnov test and expressed as mean and standard error of the mean. The comparison between groups was performed by ANOVA. The Tukey contrast (post hoc) test was used. All data were analyzed using the program Grap Pad Prism 5.00 (California) The results of the muscle mass analysis in relation to the animals' body weight showed that there was no difference between the CH, CH+AT and CH + AT + PBM groups in any of the experimental periods. The protein expression analysis by ELISA demonstrated that at 7 days there was a reduction in TNF-α levels in the CH+AT+PBM groups when compared to the CH Control group. There was no difference between the CH+AT group and the CH+AT+PBM group. After 14 days, no statistical differences were found between the different experimental groups. The results of the CSA analysis of the muscle fibers showed higher area values after 7 days in the CH+AT+PBM group, when compared to the CH+AT group CSA and smaller in area in the CH+AT group when compared to the Control CH group. After 14 days, greater area values were observed in the CH+AT+PBM group when compared to the CH + AT group. The quantitative analysis of fiber diameter showed that after 7 days there was no difference between the experimental groups and after 14 days there was an increase in the CH+AT and CH+AT+PBM groups when compared to the CH group. In conclusion, TA associated with PBM modulated the expression of TNF -α and increased CSA and muscle fiber diameter. In addition, AT performed without the association of PBM, also promoted the increase in fiber diameter.